2015
DOI: 10.1021/acsami.5b05400
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional, Porous Nickel–Cobalt Sulfide for High-Performance Asymmetric Supercapacitors

Abstract: High specific surface area, high electrical conductivity, and abundant channels have been recognized to favor pseudocapacitors, but their realization at the same time is still a great challenge. Here, we report on nickel-cobalt sulfide nanosheets (NSs) with both ultrathin thickness and nanoscale pores for supercapacitors. The porous Ni-Co sulfide NSs were facilely synthesized through micelle-confined growth and subsequent sulfuration. The NSs are as thin as several nanometers and have a large number of pores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(96 citation statements)
references
References 39 publications
6
88
1
Order By: Relevance
“…Li et al reported the facile synthesis of ultrathin nickel-cobalt sulfide nanosheets through the micelle confined growth and further sulfuration. [40] The as-synthesized nickel-cobalt sulfide nanosheets can be as thin as several nanometers and with an average pore size of ≈7 nm (Figure 6d,e). The ultrathin nickelcobalt sulfide nanosheets tended to assemble into a 3D hierarchical structure (Figure 6d).…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Li et al reported the facile synthesis of ultrathin nickel-cobalt sulfide nanosheets through the micelle confined growth and further sulfuration. [40] The as-synthesized nickel-cobalt sulfide nanosheets can be as thin as several nanometers and with an average pore size of ≈7 nm (Figure 6d,e). The ultrathin nickelcobalt sulfide nanosheets tended to assemble into a 3D hierarchical structure (Figure 6d).…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…Shen et al [27] used a hydrothermal method to prepare CoNi2S4/CNT/graphene composites which had high specific capacitance (710 F/g at 20 A/g) and the capacity retained 82% after 2000 charging-discharging cycles. Li et al [28] reported a solvothermal method to synthesize NiCo2S4 which had high specific capacitance of 1304 F/g at 2 A/g, excellent rate capability of 1116 F/g at 20 A/g. However, the disadvantages of the hydrothermal method such as long reaction time, high reaction pressure/temperature, and low production level greatly hinder large-scale production of NCS [29].…”
Section: Introductionmentioning
confidence: 99%
“…The CoSe-GkAC ASC has superior energy and power densities than that of other metal-chalcogenides based ASCs in aqueous electrolyte, such as NiTekAC (33.6 57 The high energy and power densities of CoSe-GkAC ASC could be assigned to (i) a synergistic effect between graphene and CoSe nanoparticles in the hybrid and (ii) a well developed large interfacial contact between the interfaces. Therefore, the newer CoSe-GkAC based ASC offers a potential energy storage applications.…”
mentioning
confidence: 99%